Chinesische Medizin in der Gynäkologie und Geburtshilfe: das Praxishandbuch - Römer, Ansgar (De Gruyter, 2017)
This book offers gynecologists, non-medical practitioners, and traditional Chinese medicine therapists a compact introduction to the treatment of gynecological problems, including obstetrical themes. It takes into consideration the full breadth of diagnoses in gynecology and obstetrics and describes many techniques derived from acupuncture, acupressure, Qi-Gong and nutritional medicine. --
Keywords: Chinesische Medizin; Hebamme; Geburtshilfe; Frauenkrankheit